Efeito do Hypericum perforatum em diferentes modelos de desordens motoras em ratos - Reis, Elizete de Moraes (2013)
Abnormal movements are clinical symptoms present in neurodegenerative diseases, such Parkinsonism , as well as Tardive dyskinesia. It is thought that unbalance in monoamine levels with their consequent metabolism could be involved in the etiology of these abnormal movements. However, until this moment there is not efficacious treatment with low side effects for these conditions. In this context, Hypericum perforatum (H. perforatum), popularly known as St. John s Wort, is a plant largely used as antidepressant and presenting high amount of polyphenol constituents. Its antidepressant mechanism seems to involve the increase of monoamines and monoaminoxidase inhibition. Here, we evaluated the effect of H. perforatum on different models of abnormal movements in rats, either using fluphenazine or reserpine. It were quantified the number of vacuous chewing movements (VCMs) and locomotor activity (number or rearings and crossings) in both models. In experiment 1, rats received a single administration of fluphenazine enantate (25 mg/Kg, i.m.) and/or H. perforatum (300 mg/Kg, in place of drinking water) during 7 days. Fluphenazine treatment increased VCMs and decreased the locomotor activity after 7 days of treatment. However, H. perforatum did not alter either the number of VCMs or the locomotor activity (represented by number of crossing and rearing in the open field test) in rats. In experiment 2, rats received reserpine administration once a day during 3 days (0.5 mg/Kg, s.c.) and/or H. perforatum (300 mg/Kg, in place of drinking water) during 16 days. Reserpine treatment increased VCMs and decreased the locomotor activity. H. perforatum did not alter the number of VCMs or the number of rearing. However, H. perforatum co-treatment could avoid the effect of reserpine on number of crossings. In conclusion, H. perforatum did not seem to be efficacious to protect against orofacial movements induced by fluphenazine or reserpine in rats.